Barbituric acid-modified graphitic carbon nitride nanosheets for ratiometric fluorescent detection of Cu2+. Issue 7 (1st March 2018) - Chen, Ling; Song, Zhiping; Liu, Xueting; Guo, Liangqia; Li, Mei-jin; Fu, Fengfu
Abstract : A ratiometric and visual fluorescent sensor for Cu 2+ ions based on barbituric acid-modified graphitic carbon nitride nanosheets was designed. Abstract : In this work, barbituric acid-modified graphitic carbon nitride (BCN) nanosheets with blue-green fluorescence were prepared by a copolymerization of dicyandiamide with barbituric acid and then by a chemical oxidation process. A ratiometric fluorescent sensor for Cu 2+ was designed by using BCN nanosheets as the report probe and Ru(bpy)3 Cl2 as the reference probe. In the presence of different concentrations of Cu 2+, the blue-green fluorescence of BCN nanosheets was drastically quenched, while the red fluorescence of Ru(bpy)3 Cl2 remained constant. The color of the sensor changed from blue-green to red, resulting in ratiometric and visual detection of Cu 2+ ions. The detection limit for Cu 2+ was estimated to be 70 nM, and as low as 5 μM Cu 2+ was distinguished with the naked eye. Additionally, this sensor was also applied for the detection of Cu 2+ in tap water samples.